Intensive Guidance for Taharah & Adab Class as an Effort to Instill Values of Purity and Ethics for Students of SDN Kutorejo II Pandaan, Pasuruan - Abdul Mukhlis; Ahmad Bahrurizqi Anhar; Afni Fina Afifah (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
This community engagement program aims to improve students’ understanding and practice of purity (thaharah) and ethical conduct (adab) through an intensive mentoring program titled “Taharah & Adab Class” at SDN Kutorejo II Pandaan. The main problems addressed are students’ low understanding of proper purification procedures and the decline in ethical behavior in daily interactions. The mentoring method applies a participatory approach that includes preparation, implementation, and intensive assistance stages. The program uses peer tutoring, direct practice at the ablution area, and fun-learning strategies supported by simple media such as daily control cards to monitor students’ consistency. The results show a significant improvement in the cognitive aspect, indicated by an increase in the average score from 56 to 82.6. In addition, there are observable behavioral changes in the affective and psychomotor domains. Students become accustomed to performing ablution correctly, maintaining personal hygiene, and demonstrating more polite behavior in social interactions. Teacher testimonials also confirm improvements in classroom atmosphere, which becomes more orderly and conducive to learning. The implications indicate that a practice-based and habituation-oriented mentoring model is effective in strengthening character education at the primary school level. This program can serve as a reference for developing similar initiatives that integrate religious understanding with the formation of students’ actual behavior.